ANALISIS KETIMPANGAN DISTRIBUSI PENDAPATAN PEDAGANG DI KECAMATAN TANJUNG MORAWA-DELI SERDANG - Ridho Pratama; M. Sahnan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2019)
A trader's business condition with a fairly high income uncertainty factor has an impact on the level of welfare and inequality that occur in the trader's community. The number of respondents selected to be sampled as many as 78 traders were done proportionally. The level of inequality of revenue distribution from merchants in Tanjung Morawa subdistrict is measured by the Gini Rationya value of 0.6597 or 0.6 categorized as high inequality.